How a romantic relationship can protect same‐sex attracted youth and young adults from the impact of expected rejection. Issue 8 (4th October 2014) - Baams, Laura; Bos, Henny M.W.; Jonas, Kai J.
ABSTRACT: Same‐sex attracted youth's well‐being is jeopardized by components of minority stress, but this stress can be buffered by social support. What is unknown is whether a romantic relationship can also serve as a buffer. With an online survey we examined the link between components of minority stress, psychological well‐being, and its moderated relation by romantic relationship status among 309 Dutch same‐sex attracted youth (16–24 years old, 52.9% female). The results showed that minority stress components (internalized homophobia, expected rejection, and meta‐stereotyping) were negatively related to psychological well‐being. Moderation analyses revealed that only the impact of "expected rejection" on psychological well‐being was buffered for those involved in a romantic relationship. This shows the particular functional link of romantic support in rejection contexts.